2014
DOI: 10.2217/pmt.14.13
|View full text |Cite
|
Sign up to set email alerts
|

Using Tens for Pain Control: The State of the Evidence

Abstract: Summary Transcutaneous electrical nerve stimulation (TENS) is a nonpharmacological intervention that activates a complex neuronal network to reduce pain by activating descending inhibitory systems in the central nervous system to reduce hyperalgesia. The evidence for TENS efficacy is conflicting and requires not only description but also critique. Population-specific systemic reviews and meta-analyses are emerging, indicating both HF and LF TENS being shown to provide analgesia, specifically when applied at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
267
0
16

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(285 citation statements)
references
References 99 publications
2
267
0
16
Order By: Relevance
“…The findings also indicated the value of a flexible approach to pad positioning and choice of settings including appropriate stimulation intensity 15 , that converges with recently published work highlighting the importance of these factors. 39,40 A particular strength of this research derives from the semi-structured interviews which encouraged users to express a wide range of experiences which other research methods may not have facilitated. The extensive experience of the participants contributes to the credibility of the data.…”
Section: Discussionmentioning
confidence: 99%
“…The findings also indicated the value of a flexible approach to pad positioning and choice of settings including appropriate stimulation intensity 15 , that converges with recently published work highlighting the importance of these factors. 39,40 A particular strength of this research derives from the semi-structured interviews which encouraged users to express a wide range of experiences which other research methods may not have facilitated. The extensive experience of the participants contributes to the credibility of the data.…”
Section: Discussionmentioning
confidence: 99%
“…35) However, others studies reported that blockade of peripheral opioid receptors prevented the analgesic effect produced by low, but not high frequency TENS. [35][36][37] In addition, it was known that a variety of neurotransmitters including endogenous ligand norepinephrine, GABA and serotonin were involved in analgesic actions of TENS.…”
Section: Endogenous Opioid Theorymentioning
confidence: 99%
“…11,34,35) It was also known that both TENS with high and low frequency have analgesic effects at the peripheral site by altering the excitability of peripheral nociceptors, thereby reducing pain input to the central nervous system. 35) However, others studies reported that blockade of peripheral opioid receptors prevented the analgesic effect produced by low, but not high frequency TENS. [35][36][37] In addition, it was known that a variety of neurotransmitters including endogenous ligand norepinephrine, GABA and serotonin were involved in analgesic actions of TENS.…”
Section: Endogenous Opioid Theorymentioning
confidence: 99%
“…The increased sympathetic activity is related to the risk of life (Marmar & Shivkumar, 2008), and interventions that decrease this activity reduce mortality from cardiovascular disease (ESC, 1996). In this context, TENS is presented as a potential therapeutic resource able to interact in different clinical conditions, such as hypertension, in addition to its analgesic effects widely described in literature (Chesterton et al, 2002;Sbruzzi et al, 2012;Vance et al, 2014;Bi et al, 2015). This interaction of TENS with the cardiovascular system is demonstrated by vasodilation (Cramp et al, 2000;Miller, Gruben, & Morgan, 2000;Sherry et al, 2001;Vieira et al, 2012), increased blood in peripheral and coronary blood flow (Chauhan et al, 1994;Jessurun et al, 1998;Cramp et al, 2000;Miller et al, 2000;Sandberg, Sandberg, & Dahl, 2007), decreased peripheral vascular resistance (Mannheimer, Emanuelsson, & Waagstein, 1990;Sherry et al, 2001), and heart rate (Nitz, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Transcutaneous electrical nerve stimulation (TENS) is a therapeutic modality used primarily in the management of acute and chronic pain (Chesterton, Foster, Wright, Baxter, & Barlas, 2003;Sbruzzi et al, 2012;Vance, Dailey, Rakel, & Sluka, 2014;Bi et al, 2015). The application of this resource comprises the interaction of different parameters, such as intensity, frequency, pulse duration, application time, and positioning of the electrodes (Chesterton et al, 2003).…”
Section: Introductionmentioning
confidence: 99%